A justified bad reputation after all? Dark personality traits and populist attitudes in comparative perspective - Hofstetter, Nathalie; Filsinger, Maximilian (Electoral studies, 2024)
Although scholars have extensively studied populism in recent years, the empirical exploration of dispositional or personality underpinnings of populist attitudes is still in its infancy. Especially the role played by the Dark Triad traits of Machiavellianism, narcissism, and psychopathy is strikingly understudied. The few empirical studies on this subject fail to fully capture the multi-dimensionality and non-compensatory nature of populist attitudes, are confined to particular country contexts, and produced highly inconclusive results. Specifying and expanding previous research, our main aim is to investigate the darker nuances of populists’ personalities across six European countries in 2020. Providing first cross-country evidence, our analyses reveal psychopathy as the most significant predictor of populist attitudes and their subdimensions with Machiavellianism playing a less robust role and narcissism appearing largely inconsequential. In general, most relationships seem non-universal, calling for future research into the contextuality of psychological predispositions for populist and other political attitudes.